Contemporary Clinical and Molecular Epidemiology of Vancomycin-Resistant Enterococcal Bacteremia: A Prospective Multicenter Cohort Study (VENOUS I). (23rd December 2021) - Contreras, German A; Munita, Jose M; Simar, Shelby; Luterbach, Courtney; Dinh, An Q; Rydell, Kirsten; Sahasrabhojane, Pranoti V; Rios, Rafael; Diaz, Lorena; Reyes, Katherine; Zervos, Marcus; Misikir, Helina M; et al.
Abstract: Background: Vancomycin-resistant enterococci (VRE) are major therapeutic challenges. Prospective contemporary data characterizing the clinical and molecular epidemiology of VRE bloodstream infections (BSIs) are lacking. Methods: The Vancomycin-Resistant Enterococcal BSI Outcomes Study (VENOUS I) is a prospective observational cohort of adult patients with enterococcal BSI in 11 US hospitals. We included patients with Enterococcus faecalis or Enterococcus faecium BSI with ≥1 follow-up blood culture(s) within 7 days and availability of isolate(s) for further characterization. The primary study outcome was in-hospital mortality. Secondary outcomes were mortality at days 4, 7, 10, 12, and 15 after index blood culture. A desirability of outcome ranking was constructed to assess the association of vancomycin resistance with outcomes. All index isolates were subjected to whole genome sequencing. Results: Forty-two of 232 (18%) patients died in hospital and 39 (17%) exhibited microbiological failure (lack of clearance in the first 4 days). Neutropenia (hazard ratio [HR], 3.13), microbiological failure (HR, 2.4), VRE BSI (HR, 2.13), use of urinary catheter (HR, 1.85), and Pitt BSI score ≥2 (HR, 1.83) were significant predictors of in-hospital mortality. Microbiological failure was the strongest predictor of in-hospital mortality in patients with E faecium bacteremia (HR, 5.03). The impact of vancomycin resistance on mortality in our cohort changed throughout the course of hospitalization. Enterococcus faecalis sequence type 6 was a predominant multidrug-resistant lineage, whereas a heterogeneous genomic population of E faecium was identified. Conclusions: Failure of early eradication of VRE from the bloodstream is a major factor associated with poor outcomes. Abstract : Failure to eradicate enterococci from the bloodstream in the first 4 days after the index blood culture was the most consistent factor associated with increased risk of mortality. The association of vancomycin resistance with mortality changed throughout the course of the hospitalization.